The Role of the West Aceh District Social Service in Handling Gepengs in the City of Meulaboh - Nur Era; Dar Kasih (Seutia Hukamaa Cendekia, 2023)
Beggars (tramps and beggars) are people who live as vagabonds and at the same time beg because they don't have a permanent place to live and, for various reasons, have to live under bridges, public parks, roadsides, river banks, or various other public facilities to sleep and carry out their lives. Daily. The role of Social Service is a main task of the Organizational Structure related to social problems, homeless people, beggars and other social problems. This study aims to determine the role of the Social Service in handling sprawl in Meulaboh, West Aceh District and to find out the obstacles faced by the Social Service in handling sprawl in Meulaboh in West Aceh. This research is a type of field research. The qualitative method uses data obtained from observations, interviews, and documentation, as well as data obtained from written documents related to this research. Based on the research results, it can be concluded that the role of the Social Service is beneficial in handling Gepengs in Meulaboh, and it is necessary to work together with Satpol PP, and wilayatul hisbah to raid Gepengs. The subjects in this study were the Head of the Social Service, the Head of the Rehabilitation Sector, the Head of the Rehabilitation Section, and the Beggars. Obstacles faced by the Social Service in handling sprawl in Meulaboh City, West Aceh District, include a lack of funds and facilities.